2020
DOI: 10.5812/compreped.56008
|View full text |Cite
|
Sign up to set email alerts
|

A Proactive Risk Assessment Through Healthcare Failure Mode and Effect Analysis in Pediatric Surgery Department

Abstract: Background: Patient safety is the first step to improve the quality of care. Objectives: Therefore, the present study aimed to examine the risk assessment of processes in a pediatric surgery department using the Health Failure Mode and Effect Analysis (HFMEA) in 2017 - 2018. Methods: In this research, a mixed-method design (qualitative action and quantitative descriptive cross-sectional study) was used to analyze failure mode and their effects. The nursing errors in the clinical management model were used to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 24 publications
0
20
0
1
Order By: Relevance
“…The studies proposed that FT can be a great technique to enhance training at various points of the macrocycle if it is intended to shape fundamental motor skills or remove functional restrictions (pre-hab). Based on existing insights ( Baniasadi et al, 2019 ; Abdolahi et al, 2020 ; Molavi-Taleghani et al, 2020 ) and the results shown here urges the practitioners and coaches into thinking about requesting admission for their athletes into a longer training course ( Baniasadi et al, 2019 ; Sheikhbardsiri et al, 2019 ; Sheikhbardsiri et al, 2020 ). The study’s practical application is that using FMS requirement specification can help and strength and conditioning coaches identify weaker movement patterns and improve them, effectively improving their overall training program.…”
Section: Discussionmentioning
confidence: 64%
“…The studies proposed that FT can be a great technique to enhance training at various points of the macrocycle if it is intended to shape fundamental motor skills or remove functional restrictions (pre-hab). Based on existing insights ( Baniasadi et al, 2019 ; Abdolahi et al, 2020 ; Molavi-Taleghani et al, 2020 ) and the results shown here urges the practitioners and coaches into thinking about requesting admission for their athletes into a longer training course ( Baniasadi et al, 2019 ; Sheikhbardsiri et al, 2019 ; Sheikhbardsiri et al, 2020 ). The study’s practical application is that using FMS requirement specification can help and strength and conditioning coaches identify weaker movement patterns and improve them, effectively improving their overall training program.…”
Section: Discussionmentioning
confidence: 64%
“…Aerial evaluation can help collect information regarding the exact number and amounts of damages and casualties and the needs of the area struck by the earthquake. [ 25 26 27 ]…”
Section: Resultsmentioning
confidence: 99%
“…They know that commitment to satisfying patients should be supported by a full understanding of the patient, competition, and the ability to create environments that need a change and an appropriate response to these environments. [ 26 27 ] Medical centers that can keep their patients satisfied can make them loyal to themselves and make them receive services only from these institutions for a long period of time. In fact, patient satisfaction is considered a predictor of the patient's desire to pursue treatment, return to the center, or recommend services to others.…”
Section: Discussionmentioning
confidence: 99%